Studies on Piscian Trematode Orientocreadium batrachoides[1] from Channa gachua - S. S. Nanware, D.B. Bhure* and (Recent Research in Science and Technology, 2011)
The present investigation deals with taxonomic observation of the trematode parasites Orientocreadium batrachoides [1], parasite of freshwater fish Channa gachua from Aurangabad district of M.S. India. Present worm resembles Orientocreadium batrachoides [1] in having all essential morphological characters i.e. body is elongated, small, spinose, muscular Pharynx, crescent shaped cirrus pouch and follicular vitellaria, but the same differs from it in the following character Pre pharynx absent, oral sucker smaller, ventral sucker larger, Position of testes side by side and eggs elongated. Hence it is redescribed.